Priest Under Fire : Padre David Rodríguez, the Catholic Church, and El Salvador's Revolutionary Movement - Sánchez, Peter Michael, 1954- (Book collections on Project MUSE., 2015)
Through interviews with David Rodriguez and a good helping of critical historical context, Sanchez illustrates the extent to which some religious leaders played pivotal roles in the popular movement of El Salvador's political crisis of the 1970s and 1980s.